Hubungan Status Gizi Ibu Hamil dan Pemanfaatan Pelayanan Kesehatan terhadap Kejadian BBLR - Hajar Hajar; Hasnia Hasnia; Inez Vravty Lestari; Herawaty Herawaty; Sumarni Syam (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Low Birth Weight (LBW) is one of the leading causes of neonatal mortality and contributes to an increased risk of growth and developmental disorders in later life. Maternal nutritional status during pregnancy and the utilization of antenatal health services are important factors influencing fetal growth and development. Pregnant women with poor nutritional status are at higher risk of delivering low birth weight infants due to insufficient intake of essential nutrients required during pregnancy. In addition, inadequate utilization of antenatal care services may result in delayed detection and management of pregnancy-related complications. This study aimed to determine the relationship between maternal nutritional status and the utilization of health services with the incidence of LBW. The research employed an observational analytic design with a cross-sectional approach. The study population consisted of all women who delivered in the working area of Puskesmas X in 2026. A total of 80 respondents were selected using purposive sampling. Data were collected from maternal and child health (MCH) books and medical records and analyzed using the Chi-square test. The results showed a significant relationship between maternal nutritional status and the incidence of LBW (p=0.002), as well as between the utilization of health services and the incidence of LBW (p=0.004). It can be concluded that maternal nutritional status and compliance with antenatal visits are significantly associated with LBW, highlighting the need to improve nutritional monitoring and the quality of antenatal care services.